Mutagenesis and Functional Characterization of the Four Domains of GlnD, a Bifunctional Nitrogen Sensor Protein - Zhang, Yaoping (American Society for Microbiology (ASM), 2010)
GlnD is a bifunctional uridylyltransferase/uridylyl-removing enzyme (UTase/UR) and is believed to be the primary sensor of nitrogen status in the cell by sensing the level of glutamine in enteric bacteria. It plays an important role in nitrogen assimilation and metabolism by reversibly regulating the modification of P(II) protein; P(II) in turn regulates a variety of other proteins. GlnD appears to have four distinct domains: an N-terminal nucleotidyltransferase (NT) domain; a central HD domain, named after conserved histidine and aspartate residues; and two C-terminal ACT domains, named after three of the allosterically regulated enzymes in which this domain is found. Here we report the functional analysis of these domains of GlnD from Escherichia coli and Rhodospirillum rubrum. We confirm the assignment of UTase activity to the NT domain and show that the UR activity is a property specifically of the HD domain: substitutions in this domain eliminated UR activity, and a truncated protein lacking the NT domain displayed UR activity. The deletion of C-terminal ACT domains had little effect on UR activity itself but eliminated the ability of glutamine to stimulate that activity, suggesting a role for glutamine sensing by these domains. The deletion of C-terminal ACT domains also dramatically decreased UTase activity under all conditions tested, but some of these effects are due to the competition of UTase activity with unregulated UR activity in these variants.